Development and characterization of roselle fibre reinforced vinyl ester composites - Razali, Nadlene (2016)
Recently, in line with numerous raising environmental concerns, researchers are now replacing synthetic fibers with natural fibers as the main component in composites. Natural fibers are preferred compared to synthetic fibers due to several imminent advantages, such as biodegradable, light in weight, low in cost, and good mechanical properties. With such attributes, roselle is a plant that has been found to be suitable to be used to produce natural fibers. Hence, this research focused on the capability and the sustainability of roselle fiber as lignocellulosic reinforcement for polymer composites. For that purpose, this research had been comprised of four parts. The first part refers to characterization of roselle fiber as a reinforcement material in terms of its mechanical, thermal, physical, morphology, and chemical properties. In this part, the roselle fiber had been compared to other established natural fibers, such as kenaf and jute. The results obtained indicated that the moisture content of roselle fiber was 10.867%, while water absorption was 286.4714%. On top of that, the thermal gravimetric analysis (TGA) was conducted to determine the thermal stability of roselle fiber at high temperature. The results showed that the initial degradation of roselle fiber started at 2250C and the decomposition of lignocellulosic component was completed at 400 0C. Furthermore, tensile test was conducted to investigate the mechanical properties of roselle fiber. The tensile strength of roselle fiber had been 130-562 MPa. Thus, on the basis of the identified properties, the roselle fiber has been proven to be one of the good and natural fibers that can be used as a reinforced material for manufacturing of polymer composites for different applications, besides saving the cost required to manage agro waste. Next, the second part of this research looked into the effect of plant age (3, 6, and 9 months) upon physical, morphological, chemical, thermal, and mechanical properties. The highest yields of the properties were used for the next study in this research. From the results retrieved, it had been observed that the diameter of roselle fiber increased as the plant attained maturity. However, in contrast to this, the moisture content and the water absorption of roselle fiber decreased as the plant began to mature. Moreover, the chemical content of roselle fibers from plants of different ages indicated that as the plant matured, the cellulose content decreased. In addition, the tensile strength of roselle fiber decreased from 3 months old to 9 months old. Meanwhile, the thermal analysis results showed that the effect of thermal decomposition of roselle fiber was almost similar for all plant ages. Nevertheless, the 3-month-old roselle fiber displayed the highest yield in mechanical properties. Thus, 3-month-old roselle fiber was used as reinforcement material for the next study, which included the treatment and the composites analysis. Moving on, the third part of this research investigated the effect of chemical treatment upon roselle fiber. This study examined chemical, physical, thermal, mechanical, and morphological characteristics of roselle fiber-reinforced vinyl ester (RFVE) subjected to different fiber treatments. The roselle fiber was treated with alkalization and a silane coupling agent. The treated roselle fiber significantly enhanced most of the properties of vinyl ester (VE) biocomposites compared to those of untreated biocomposite. The results further revealed that alkalization and silane treatments of the fiber changed its chemical properties. The treated fiber improved the attribute of water repellence of the RFVE compared to that of untreated fiber. In addition, the use of silane coupling agent was determined as the best chemical treatment for optimum water absorption effect. Besides, TGA demonstrated that alkalization-treated fiber had improved thermal stability; however, the opposite result was obtained with the silane-treated fiber. Nonetheless, the morphological examination of both treated and untreated RFVE exhibited good fiber adhesion between the treated fiber and the matrix, and less fiber pull-out from the matrix was observed. This observation, particularly, provides a good indication of the interfacial interlocking between the fiber and the matrix, which improved the tensile properties of the composites. In contrast, the impact results revealed that the treated fiber had decreased impact energy compared to that of untreated fiber. Finally, the last part of this research evaluated the mechanical properties (tensile, flexural, and impact strength) and the thermal properties of RFVE subjected to fiber loading. The composites samples were prepared with two different parameters; with fiber contents of 10%, 20%, 30%, and 40 vt%, as well as without fiber (neat VE). The morphological properties of impact fracture samples were studied by using Scanning electron microspcope (SEM). From the examination, the RFVE composite had been found to increase both the tensile strength and the tensile modulus. In fact, the highest tensile strength and modulus had been observed at 20 vt % of fiber loading. However, a decrement was noted on the impact and the flexural strength with the increase in fiber loading. Nevertheless, the SEM showcased good fiber/matrix adhesion and fiber dispersion at 20% fiber loading, which reflected the good properties of tensile strength. However, the agglomeration of the fiber was seen at higher fiber loading. In addition, the TGA and the DTG curves showed three major degradations of RFVE in terms of the loss of moisture content, as well as the degradation of hemicelluloses and cellulose. Other than that, the thermal analysis showed enhancement in the residual content of the composite materials, thereby improving thermal stability. However, no significant difference was observed for degradation in temperature subjected to fiber loading.